Lewy Body Disease is a Contributor to Logopenic Progressive Aphasia Phenotype. Issue 3 (17th December 2020) - Buciuc, Marina; Whitwell, Jennifer L.; Kasanuki, Koji; Graff‐Radford, Jonathan; Machulda, Mary M.; Duffy, Joseph R.; Strand, Edythe A.; Lowe, Val J.; Graff‐Radford, Neill R.; Rush, Beth K.; Franczak, Malgorzata B.; Flanagan, Margaret E.; et al.
Abstract : Objective: The objective of this study was to describe clinical features, [ 18 F]‐fluorodeoxyglucose (FDG)‐positron emission tomography (PET) metabolism and digital pathology in patients with logopenic progressive aphasia (LPA) and pathologic diagnosis of diffuse Lewy body disease (DLBD) and compare to patients with LPA with other pathologies, as well as patients with classical features of probable dementia with Lewy bodies (pDLB). Methods: This is a clinicopathologic case‐control study of 45 patients, including 20 prospectively recruited patients with LPA among whom 6 were diagnosed with LPA‐DLBD. We analyzed clinical features and compared FDG‐PET metabolism in LPA‐DLBD to an independent group of patients with clinical pDLB and regional α‐synuclein burden on digital pathology to a second independent group of autopsied patients with DLBD pathology and antemortem pDLB (DLB‐DLBD). Results: All patients with LPA‐DLBD were men. Neurological, speech, and neuropsychological characteristics were similar across LPA‐DLBD, LPA‐Alzheimer's disease (LPA‐AD), and LPA‐frontotemporal lobar degeneration (LPA‐FTLD). Genetic screening of AD, DLBD, and FTLD linked genes were negative with the exception of APOE ε4 allele present in 83% of LPA‐DLBD patients. Seventy‐five percent of the patients with LPA‐DLBD showed a parietal‐dominant pattern of hy pometabolism; LPA‐FTLD – temporal‐dominant pattern, whereas LPA‐AD showed heterogeneous patterns of hypometabolism. LPA‐DLBD had more asymmetrical hypometabolism affecting frontal lobes, with relatively spared occipital lobe in the nondominantly affected hemisphere, compared to pDLB. LPA‐DLBD had minimal atrophy on gross brain examination, higher cortical Lewy body counts, and higher α‐synuclein burden in the middle frontal and inferior parietal cortices compared to DLB‐DLBD. Interpretation: Whereas AD is the most frequent underlying pathology of LPA, DLBD can also be present and may contribute to the LPA phenotype possibly due to α‐synuclein‐associated functional impairment of the dominant parietal lobe. ANN NEUROL 2021;89:520–533